Faktor-Faktor Yang Berhubungan dengan Pemanfaatan Pelayanan ANC di Wilayah Kerja Puskesmas Pargarutan Tahun 2023 - Endang Purnama; Erin Padilla Siregar; Amelia Erawaty Siregar (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2023)
Components that influence the use of health services are based on Andersen's (1995) theory which explains that there are three main factors that influence a person's actions in using health services, namely predisposing factors, enabling factors and need. The aim of this research is to analyze the factors that influence the utilization of Antenatal Care services at the Pargarutan Tapanuli Selatan Community Health Center. 1 Utilization of antenatal care services Utilization of antenatal care services. ANC utilization is the use of ANC services by pregnant women to check their pregnancy at a health service center in accordance with the provisions for the use of antenatal care services, namely, once in the first trimester, once in the second trimester, and at least twice in the third trimester. The type of research used in this research is quantitative research with a cross-sectional research design. The variable that has no effect on the use of ANC services is the work variable with a p value = 0.354 (>0.05). The attitude variable has a 2 times greater influence (with a value of Exp(B)= 2.566) on utilizing ANC services than the variable of knowledge and family support for pregnant women to pay attention to their womb by carrying out ANC checks at health services regularly so that it can be monitored by health workers.